Human resources quality improvement from the perspective of Kaizen practice - Minh Nguyen Dat; Quyen Nguven Thi Hanh (Zielona Góra: Faculty of Economics and Management Press)
Kaizen has long been known as an improvement philosophy that starts with small frequent changes to make larger changes in production. These changes come from the ideas and creative thinking of employees to ensure that the production conditions and processes are continuously improved. However, Kaizen not only helps motivate employees to think creatively with effective methods and skills, but it also helps them develop their capabilities, personality, and good work habits.
Keywords: Kaizen; human factors; human resources quality; operational performance; LEAN manufacturing; czynniki ludzkie; jakość zasobów ludzkich; wydajność operacyjna; odchudzona produkcja